METODE BIMBINGAN KONSELING MENURUT INJIL SINOPTIK DAN IMPLIKASINYA DALAM PELAKSANAAN BIMBINGAN KONSELING OLEH GURU AGAMA KRISTEN - Maya Kristina Situmeang (Metanoia, 2022)
Education is one of human efforts to equip what is lacking in human nature, by growing, developing, maturing and elevating humans to the human level. It aims to find out the meaning of counseling guidance according to the Synoptic Gospels, how it is implemented by Christian religious teachers and know the implications. The method of counseling guidance according to the Synoptic Gospels means the way the counselor helps the counselee to go through the counseling process similar to Jesus' example when guiding counseling people in the Synoptic Gospels in Matt. 18: 1-5, Mk 9: -37, Luke 9: 46-48) . Researchers chose to use qualitative research methods because they aimed to obtain a comprehensive picture and understanding of the implications of the implementation of the guidance and counseling method according to the Synoptic Gospels by Christian religious teachers. Data obtained by observation and interview. The research results obtained in the description and in the form of narrative research are not numbers as quantitative research. The results of this study indicate that counselors use the guidance of counseling conducted by Jesus in the Synoptic Gospels.